On the piezotronics and tactile sensing virtual simulation. Issue 1 (25th October 2016) - Chiroiu, Veturia
Abstract: A flexible finger with muscles made of Nitinol wires and the skin made of auxetic material is analyzed from the tactile sensing point of view. The recognizing of the shape and texture of 3D objects is performed by simulation the action of an array of nanopiezotronic transistors integrated into the skin. The array of nanopiezotronic transistors makes possible the detection of the pressure‐induced changes in the auxetic skin. The shape and texture of the objects is best estimated by determining the surface and texture as an n ‐ellipsoid defined by 12 parameters. An inverse problem is solved in order to find these parameters from the condition that the n ‐ellipsoid best fits the set of data points probed by touch with the finger. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)